Innate Immune Responses by Respiratory Viruses, Including Rhinovirus, During Asthma Exacerbation - Nakagome, Kazuyuki; Nagata, Makoto (Frontiers in Immunology, 2022)
Viral infection, especially with rhinovirus (RV), is a major cause of asthma exacerbation. The production of anti-viral cytokines such as interferon (IFN)-β and IFN-α from epithelial cells or dendritic cells is lower in patients with asthma or those with high IgE, which can contribute to viral-induced exacerbated disease in these patients. As for virus-related factors, RV species C (RV-C) induces more exacerbated disease than other RVs, including RV-B. Neutrophils activated by viral infection can induce eosinophilic airway inflammation through different mechanisms. Furthermore, virus-induced or virus-related proteins can directly activate eosinophils. For example, CXCL10, which is upregulated during viral infection, activates eosinophils in vitro. The role of innate immune responses, especially type-2 innate lymphoid cells (ILC2) and epithelial cell-related cytokines including IL-33, IL-25, and thymic stromal lymphopoietin (TSLP), in the development of viral-induced airway inflammation has recently been established. For example, RV infection induces the expression of IL-33 or IL-25, or increases the ratio of ILC2 in the asthmatic airway, which is correlated with the severity of exacerbation. A mouse model has further demonstrated that virus-induced mucous metaplasia and ILC2 expansion are suppressed by antagonizing or deleting IL-33, IL-25, or TSLP. For treatment, IFNs including IFN-β suppress not only viral replication but also ILC2 activation in vitro. Agonists of toll-like receptor (TLR) 3 or 7 can induce IFNs, which can then suppress viral replication and ILC2 activation. Therefore, if delivered in the airway, IFNs or TLR agonists could become innovative treatments for virus-induced asthma exacerbation.